Historians of Israel ; v.2 - Anderson, Hugh (London, UK Lutterworth, 1962)
Contents : v. 2 : 1 and 2 Chronicles, Ezra, Nehemiah
Keywords: Bible. O.T. Chronicles -- criticism, interpretation, etc; Bible. O.T. Ezra -- criticism, interpretation, etc; Bible. O.T. Nehemiah -- criticism, interpretation, etc